A survey on the public relations techniques of selected hospital libraries in Quezon City - Emano, Judy Ann M. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This study is a survey about the public relations technique of selected hospital libraries in Quezon City. The objectives of the study are: to identify the public relations techniques being implemented by the three hospital libraries; to find out who are the active users of the library; to determine if the library users know about their hospital's specialization; to find out what collection resources in the library are utilized and underutilized and to give recommendations on how to further promote services/resources in their hospital libraries.
This study covers three hospital libraries, those of National Kidney and Transplant Institute (NKTI), Lung Center of the Philippines (LCP) and Philippine Heart Center (PHC). The respondents in this study are the doctors, nurses, and administrative and allied health support staff.
Three hundred thirty six (336) library users were the respondents identified. The survey results revealed that the following techniques for public relations being implemented in three hospital libraries are the following: Hospital Orientation; Hospital Website; Hospital Publication; Booklist; Annual Reports; Meetings and Billboards. Activities made in the library are to read books; browse new journals, read newspapers, search the Internet. The primary active users of the three libraries are the doctors, followed by the nurses and the administrative and allied health staff. Although they frequently visit the library, they are not aware of other services and resources that are available in their library. Recommendations offered are:1.) to further develop of the library orientation program; 2.) the production of attractive handouts and informative brochures for the library; 3) current awareness program to be posted on billboards, electronic boards and e-mails; 4) develop a separate library homepage which can be linked to the institutions; 5) publish library newsletters that include the new acquisitions, new activities and developments happening in the library; 6) set up displays in the front area within the library or even in the hospital lobby and 7) to hold book exhibits and book fairs.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Hospital libraries -- Philippines -- Quezon City -- Public relations